Injuries of Tsunami's Victims in Phang-Nga Province - ฉายคุณรัฐ, เจษฎา (Disease Control Journal, 2010)
This descriptive study was aimed to delineate the situations of injuries and deaths from tsunami including characteristics of injuries and wounds, daily expenses and length of hospital admission. Data of patients and expenses for treatment were collected from those patients who were injured due to Tsunami and had the treatment at Takaopa and Phang-Nga hospital during December 26, 2004 to January10, 2005. The results revealed that total of 3,057 cases were sent to the hospitals. About 96.5 percent of them received proper treatment and 3.44 percent were died during ambulation. Both OPD and IPD cases were cured at 87.63 percent and 0.18 percent died while 12.19 percent were referred to center hospital. The age group of 60 years up had the highest case fatality rate. Most of injuries were abrasion wound (43 percent) and slightly injuries (75.26 percent). The average cost of treatment of out patients and in patients were 264.36 and 9,947.50 Baht respectively. The average cost of small wound operation and general operation were 1,798.42 and 16,792.07Baht respectively. The average length of hospital admission in intensive care units and general wards were 4.6 and 4.3 days respectively. We learnt that hospital preparedness plan for massive injury needed to be well planned while the team, equipment, medicine and facilities including transportation should be in readiness.